Household Energy Choice for Cooking Fuel and Underlying Circumstances in Non-Formal Urban Settlements in Kenya - Oluoch, Dan Oduor; Nyamasyo, Gideon (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2020)
This study investigated the choice of cooking fuel and underlying circumstances in Kibra slums in Nairobi County, Kenya. The study focused on various factors that influence household choice of cooking fuel and those which could keep household away from using other cooking fuels in non-formal settlements areas in the urban set-up. The study was both quantitative and qualitative and used questionnaires and observation schedules to collect data among targeted households. The findings suggest that various factors play crucial roles in determining household choice of improved fuel for cooking but most dominant factors were; time spent to cook a meal, ease of lighting, affordability, availability of fuel and its storage. The study also realized that lack of sufficient income has little influence on people to adopt or reject improved fuels. The paper argues that more data and necessary information need to be provided on the merits and demerits of various types of improved cooking fuel to the household in the slums and the its environs to enable the residents make better choices. The findings of this study indicated that for fuel choice at various household levels, it is still a challenge as some of the households targeted did not have any good reason why they use their preferred fuel type and have no much knowledge on any dangers associated with their cooking fuel choices apart from when they witness an incidence or incidence which could be considered as dangerous.